2D Carbon Fiber Reinforced High Density Polyethylene Multi-Layered Laminated Composite Panels: Structural, Mechanical, Thermal, and Morphological Profile. Issue 10 (October 2016) - Khan, Shahzad Maqsood; Gull, Nafisa; Munawar, Muhammad Azeem; Islam, Atif; Zia, Saba; Shafiq, Muhammad; Sabir, Aneela; Awais, Syed Muhammad; Butt, Muhammad Arif; Butt, Muhammad Taqi Zahid; Jamil, Tahir
Abstract : Carbon fiber reinforced high density polyethylene multi-layered laminated composite panels (HDPE/CF MLCP) with excellent in-plane properties along transverse direction have been formulated. Composite architectures with carbon fiber (CF) designed in 2D layout in conventional composites can alleviate their properties in thickness direction, but all attempts so far developed have achieved restrained success. Here, we have exposed an approach to the high strength composite challenge, without altering the 2D stack design on the basis of concept of fiber reinforced laminated composites that would provide enhanced mechanical and thermal properties along transverse direction. CF sheets allowed the buckling of adjoining plies in 2D MLCP. We fabricated 2D MLCP by stacking the alternative CF and HDPE layers under different loading conditions, which resulted in high strength composites. These plies of CF and HDPE served as unit cells for MLCP, with CF offering much-needed fracture toughness and hardness to these materials. For 2D HDPE/CF MLCP, we demonstrated noteworthy improvement in physical and chemical interaction between CF and HDPE, in-plane fracture strain, flexural strength (30.684 MPa), bending modulus (7436.254 MPa), thermal stability (40.94%), and surface morphology, upon increasing the CF layers up to twenty, enabling these composites truly for high temperature and high strength applications.